Relative atomic mass scale. A teaching aid - Baumgartner, Erwin; Benítez, Carlos; Fernández Cirelli, Alicia; Lastres Flores, Luz (American Chemical Society, 1988)
Fil: Baumgartner, E. Comisión Nacional de Energía Atómica; Argentina